Lupus antibodies induce behavioral changes mediated by microglia and blocked by ACE inhibitors - Nestor, Jacquelyn (J Exp Med, 2018)
Cognitive impairment occurs in 40–90% of patients with systemic lupus erythematosus (SLE), which is characterized by autoantibodies to nuclear antigens, especially DNA. We discovered that a subset of anti-DNA antibodies, termed DNRAbs, cross reacts with the N-methyl-d-aspartate receptor (NMDAR) and enhances NMDAR signaling. In patients, DNRAb presence associates with spatial memory impairment. In a mouse model, DNRAb-mediated brain pathology proceeds through an acute phase of excitotoxic neuron loss, followed by persistent alteration in neuronal integrity and spatial memory impairment. The latter pathology becomes evident only after DNRAbs are no longer detectable in the brain. Here we investigate the mechanism of long-term neuronal dysfunction mediated by transient exposure to antibody. We show that activated microglia and C1q are critical mediators of neuronal damage. We further show that centrally acting inhibitors of angiotensin-converting enzyme (ACE) can prevent microglial activation and preserve neuronal function and cognitive performance. Thus, ACE inhibition represents a strong candidate for clinical trials aimed at mitigating cognitive dysfunction.